71. MGMT PROMOTER METHYLATION IS A PROGNOSTIC BIOMARKER IN EGFR MUTANT LUNG ADENOCARCINOMA WITH BRAIN METASTASES. (4th August 2020) - Mamatjan, Yasin; Zuccato, Jeffrey; Moraes, Fabio; Cabanero, Michael; Shali, Wumairehan; Weiss, Jessica; Tsao, Ming; Aldape, Kenneth; Shepherd, Frances; Zadeh, Gelareh
Abstract: EGFR-mutant lung adenocarcinomas (EGFRm-LUAD) have a higher risk of brain metastasis (BM) development than non-mutant lesions regardless of cancer stage. BM development is a marker of tumor aggressiveness and has significant prognostic impact that leads to treatment failure. MGMT promoter methylation is known to determine response to therapy in other cancer types but it has not been investigated in EGFRm-LUAD brain metastases. This work aims to assess whether MGMT promoter methylation predicts patient survival or BM development in EGFRm-LUAD patients. A large cohort of 90 primary EGFRm-LUAD, 33(37%) of which developed BM, were profiled using Illumina Infinium MethylationEPIC Beadchip. We utilized genome-wide methylation signatures to determine MGMT methylation status using the previously reported MGMT-STP27 approach that uses two CpG sites to predict MGMT methylation status. Cox modeling was performed to assess whether MGMT methylation status correlates with overall survival independent of other clinical factors. MGMT methylation significantly predicted poorer survival in EGFRm-LUAD patients developed BM (p=0.0003) and those who did not (p=0.003). A multivariate Cox analysis, adjusting for stage and smoking status as potential confounders, showed that MGMT methylation (HR=6.2, 95%CI:2.2–17.4, p=0.0005) and BM (HR=2.6, 95%CI:1.3–5.3, p=0.007) were both independently predictive of worsened survival. Total Mutation Burden calculated by the number of mutations per megabase of DNA was higher in MGMT methylated tumours with an interquartile range (IQR) of 58(30–71) compared to MGMT unmethylated tumours with IQR of 5.5(4.3–6.1). This work shows that MGMT promoter methylation status is an important prognostic biomarker in EGFRm-LUAD patients. Further work will validate these findings obtained using whole-genome DNA methylation by comparing to results using methylation specific PCR assays. MGMT promoter methylation status in EGFRm–LUAD patients with BM may be used to guide patient treatment with potentially a greater extent of treatment for those higher risk patients.